Little women - DiNovi, Denise; Swicord, Robin; Armstrong, Gillian 1950-.; Ryder, Winona 1971-.; Sarandon, Susan 1946-.; Byrne, Gabriel 1950-.; Alvarado, Trini; Mathis, Samantha; Dunst, Kirsten; Danes, Claire 1979-.; Columbia Pictures; DiNovi Pictures (Firm). ([Culver City, Calif.] Columbia Pictures, 1994)
A classic coming-of-age story set during the Civil War, "Little Women" follows the childhood adventures of the four free-spirited March sisters. With their father away fighting in the Civil War, Joe, Meg, Beth and Amy grow up with their mother in somewhat reduced circumstances. They are a close family who inevitably have their squabbles and tragedies. But the bond holds even when, later, men friends start to become a part of the household.
Summary from the website: http://www.imdb.com/title/tt0110367/plotsummary.
Based upon the novel by Louisa May Alcott.
Title from container.
Originally released as VHS by Magnavision Inc.
Screenplay, Robin Swicord ; producer, Denise DiNovi.
Winona Ryder (Jo March), Gabriel Byrne (Friedrich Bhaer), Trini Alvarado (Meg March), Samantha Mathis (Older Amy March), Kirsten Dunst (younger Amy March), Claire Danes (Beth March), Christian Bale (Laurie), Eric Stoilz (John Brooke), Mary Wickes (Aunt March) and Susan Saradon (Mrs. Abigail "Marmee" March).
Rated PG.
Keywords: Mothers and daughters -- Drama; Daughters -- Drama; Feature Films; Families in motion pictures